Improvements in Intra-European Inter-City Flight Connectivity: 1996-2004 - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2006)
This paper examines the dramatic improvement in inter-city connectivity by focusing on scheduled passenger air service linking the United Kingdom and Ireland with continental Europe. Between 1996 and 2004, inter-city connectivity as defined by the operation of scheduled non-stop service improved dramatically in two key ways: the number of cities served (increased by 40% from 94 to 135) and the number of city-pairs served (increased by 91% from 224 to 428). A large portion of this increase is attributable to the new generation of low-fare carriers. This improvement in inter-city connectivity benefited a large number of small, provincial towns with no adverse impact on flights out of traditional gateway cities and capitals.